Laughing With Science: The Influence of Audience Approval on Engagement. Issue 2 (April 2020) - Cacciatore, Michael A.; Becker, Amy B.; Anderson, Ashley A.; Yeo, Sara K.
While there is mounting evidence that humor can be an effective means of engaging publics, much remains to be learned about the contextual factors that shape how audiences receive and process humorous scientific content. Analyzing data from a controlled experiment ( N = 217), this study explores the differential impact of exposure to stand-up comedy featuring a scientist that generates considerable laughter from the audience versus stand-up comedy lacking audience reaction. Among the key findings, audience laughter served to heighten the affective response of viewers, and affective response was positively linked to two forms of audience engagement with science.